2023
DOI: 10.31234/osf.io/p8eay
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engaging Students with Interactive Education: The Motivational Qualities of Student Response Systems

Abstract: Educators have incorporated technologies designed to ‘gamify’ or increase the fun and reward in classroom learning. One of them, the student response systems (SRS), is increasingly used, but little is known about how it can best be employed to create positive learning climates. Informed by self-determination theory (SDT), a study - separated into two experiments - investigated the role of SRS as an educational tool and its relationship with academic well-being outcomes that have previously been linked to posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 58 publications
2
3
0
Order By: Relevance
“…These findings build on previous research (David & Weinstein, 2023), which suggested that GET enhanced the learning experience, but only when gamified experiential strategies were in use. When students engaged in GET as part of a team, had the choice to participate, or engaged in friendly competition, they felt need satisfied, which correlated with more self-reported effort and interest in contrast to using GET anonymously or when answering the same questions on paper.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These findings build on previous research (David & Weinstein, 2023), which suggested that GET enhanced the learning experience, but only when gamified experiential strategies were in use. When students engaged in GET as part of a team, had the choice to participate, or engaged in friendly competition, they felt need satisfied, which correlated with more self-reported effort and interest in contrast to using GET anonymously or when answering the same questions on paper.…”
Section: Discussionsupporting
confidence: 88%
“…For example, Sun and Hsieh (2018) conducted an experiment on 118 junior high school students and two teachers and found that making friendly competition salient can increase intrinsic motivation and engagement. Similar findings for friendly competition were identified in a brief classroom experiment with younger students (David & Weinstein, 2023).…”
Section: A Gamified Experiential Learning Intervention For Engaging S...supporting
confidence: 80%
See 3 more Smart Citations